Emotional Intelligence, Organizational Commitment, and Organizational Citizenship Behavior on Employee Performance of Manufacturing Company - Iyar Sasavila Aypik; Fadhistia Fadhistia; Siti Maryam (CV. AFDIFAL MAJU BERKAH, 2025)
High-quality, adaptive, and change-oriented human resources are very important for companies to sustain themselves in the midst of the increasingly rapid currents of globalization. This study had the aim to analyze the effects of emotional intelligence, organizational commitment, as well as Organizational Citizenship Behaviour (OCB) on employee performance at manufacturing company. The method used was quantitative, using primary and secondary data. The population consisted of 594 employees working in the production department, with a sample of 239 respondents calculated with the use of the Slovin formula at a 5% error margin. Data were analyzed through Smart PLS version 3.0. This study’s findings concluded that emotional intelligence, organizational commitment, as well as OCB positively and significantly affect employee performance. Simultaneously, these three variables contribute to the improvement of employee performance, with complementary effects that support the achievement of company goals.